2018
DOI: 10.3390/jcm7120547
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Technical Difficulties in Laparoscopic Splenectomy and Analysis of Risk Factors for Postoperative Complications in 468 Cases

Abstract: Prediction of intraoperative difficulties may be helpful in planning surgery; however, few studies explored this issue in laparoscopic splenectomy (LS). We performed retrospective analysis of consecutive 468 patients undergoing LS from 1998 to 2017 (295 women; median age 47 years). The patients were divided into difficult LS and control groups. The inclusion criteria for difficult LS were operative time ≥mean + 2SD; intraoperative blood loss ≥500 mL, intraoperative adverse events (IAE), conversion. Primary out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Splenectomies are often viewed as learning procedures [ 34 ]. The data presented here further reminds the surgical community that these procedures pose a significant risk for the development of POPF and experienced (pancreatic) surgeons should be present, especially in the case of a difficult situs [ 30 , 39 , 49 , 50 ]. It is also reasonable to advocate that patients with a certain risk profile needing a PSE or patients with an expected SSE should be presented at a center with expertize not only in splenic surgery but also in pancreatic surgery, to avoid failure to rescue in cases with complicated postoperative courses due to POPF [ 50 ].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Splenectomies are often viewed as learning procedures [ 34 ]. The data presented here further reminds the surgical community that these procedures pose a significant risk for the development of POPF and experienced (pancreatic) surgeons should be present, especially in the case of a difficult situs [ 30 , 39 , 49 , 50 ]. It is also reasonable to advocate that patients with a certain risk profile needing a PSE or patients with an expected SSE should be presented at a center with expertize not only in splenic surgery but also in pancreatic surgery, to avoid failure to rescue in cases with complicated postoperative courses due to POPF [ 50 ].…”
Section: Discussionmentioning
confidence: 76%
“…Indications for PSE often include splenomegaly and the size of the spleen has been suggested to be a risk factor for the development of POPF [ 29 , 30 ]. In addition, Targarona et al identified splenic weight as a risk factor for postoperative complications [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative abdominal bleeding is a major cause of conversion to open surgery. It has been reported that a spleen length ≥19 cm is a risk factor for difficult LS and intraoperative hemorrhage (24). No significant difference in HVPG was found between the 2 groups; however, the diameters of the splenic and portal veins in the MS group were much larger than those of the MMS group, indicating that more portal-systemic collaterals formed in the MS group.…”
Section: Discussionmentioning
confidence: 76%
“…In all three cases, the intraoperative bleeding was secondary to difficult access to the splenic hilum and inadequate vascular control. The correlation between large spleen size and increased risk of intraoperative bleeding during splenectomy has been reported in the published literature [ 24 - 25 ].…”
Section: Discussionmentioning
confidence: 99%